"I DON'T WANT TO BOTHER ANYONE" OR HELP-SEEKING PATTERNS OF VIETNAMESE FAMILY CAREGIVERS IN DEMENTIA CARE. (16th November 2018) - Nguyen, T
Abstract: Dementia is one of the leading health burdens among older adults in Vietnam. However, very little is known about Vietnamese family caregivers in dementia care, particularly their help-seeking, in their unique culture and changing context. This paper aims to examine their help-seeking perception and patterns throughout the process of caregiving for relatives with dementia. Adopting the constructivist grounded theory approach, 30 face-to-face, semi-structured interviews, including 10 follow-up interviews, were conducted in Vietnamese language with 20 primary family caregivers (13 females and seven males, aged 34 to 86) of people diagnosed with dementia (aged 57 to 88) from a national geriatric hospital in Vietnam. Interview transcripts in Vietnamese were analyzed with the program MaxQDA12 and followed a three-phase coding procedure (initial coding, focused coding, and theoretical coding). Results show that Vietnamese family caregivers highly valued independence, self-devotion, and self-sacrifice which motivated them to endure caregiving independently and delayed their help-seeking. They only sought help when the situations were considered 'out-of-hand.' Their help-seeking process was iterative and started with disease and caregiving experience. In the next phase of cognitive appraisal, caregivers clarified problems (medical decision-making, interpersonal communication, task sharing, caregiving emergency, and self-care) and identified appropriate, available formal and informal sources before reaching out for help. Family was considered the primary source for help-seeking. Help-seeking outcomes shaped caregivers' intention and strategies to continue to seek help for other problems. Study results call for further studies and advocate the needs of culturally competent services targeting Vietnamese family caregivers in their cultural context.